Neutrino Target-of-Opportunity Observations with Space-based and Suborbital Optical Cherenkov Detectors - Venters, Tonia M.; Reno, Mary Hall; Krizmanic, John F.; Olinto, A. V.; Adams, J. H.; Aloisio, R.; Anchordoqui, L. A.; Anzalone, A.; Bagheri, M.; Barghini, D.; Battisti, M.; Bergman, D. R.; et al. (Proceedings of Science, 2022)
Cosmic-ray accelerators capable of reaching ultra-high energies are expected to also produce very-high energy neutrinos via hadronic interactions within the source or its surrounding environment. Many of the candidate astrophysical source classes are either transient in nature or exhibit flaring activity. Using the Earth as a neutrino converter, suborbital and space-based optical Cherenkov detectors, such as POEMMA and EUSO-SPB2, will be able to detect upward-moving extensive air showers induced by decaying tau-leptons generated from cosmic tau neutrinos with energies ∼ 10 PeV and above. Both EUSO-SPB2 and POEMMA will be able to quickly repoint, enabling rapid response to astrophysical transient events. We calculate the transient sensitivity and sky coverage for both EUSO-SPB2 and POEMMA, accounting for constraints imposed by the Sun and the Moon on the observation time. We also calculate both detectors' neutrino horizons for a variety of modeled astrophysical neutrino fluences. We find that both EUSO-SPB2 and POEMMA will achieve transient sensitivities at the level of modeled neutrino fluences for nearby sources. We conclude with a discussion of the prospects of each mission detecting at least one transient event for various modeled astrophysical neutrino sources.
CRIS-Team Scopus Importer:2024-12-16